Integrating Curriculum Innovation and Adaptive Learning Design to Promote Meaningful Learning in Higher Education - Sri Puguh Kristiyawati; Fakhruddin Fakhruddin; Suwito Eko Pramono; Tri Joko Raharjo (Universitas Negeri Semarang, 2026)
Digital technology transformation, changing labor market demands, and the diversity of student characteristics require higher education institutions to continuously innovate their curricula and renew their learning design. Curriculum can no longer be understood merely as a list of courses, but as a structured learning experience that connects learning outcomes, graduate competencies, instructional strategies, assessment, and the needs of society and the labor market. This article aims to analyze the integration of curriculum innovation and adaptive learning design in promoting meaningful learning in higher education. This article employs a conceptual literature review approach by examining relevant publications from the last five years on competency-based curriculum, outcome-based education, adaptive learning, student-centered learning, blended learning, and artificial intelligence in higher education. The findings indicate that curriculum innovation should be directed toward learning flexibility, competency strengthening, alignment with labor market needs, and continuous evaluation. Meanwhile, adaptive learning design is needed to adjust learning strategies, media, activities, and assessment to the diverse needs of students. The integration of these two aspects can promote meaningful learning because students do not only understand concepts, but are also able to connect theory with real-life experiences, think critically, solve problems, and develop professional competencies. This article offers a conceptual framework suggesting that meaningful learning can be achieved through an integrated relationship among curriculum innovation, adaptive learning design, digital technology, and student-centered learning.